Sistem Pertambangan Koridor dalam Perspektif Hukum Islam (Studi Kasus di Kampung Mayang Mangurai Kecamatan Teluk Bayur Kabupaten Berau): Mining Corridors from an Islamic Legal Perspective (Case Study in Mayang Mangurai Village, Teluk Bayur District, Berau Regency) - Musriwan, Musriwan; Muchtar, Andi Dahmayanti; Sarni, Santi; Idris, Risdayani; Nurul Kharisma Idrus (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study examines corridor mining practices, namely informal and illegal coal mining carried out by landowners and unofficial miners in Kampung Mayang Mangurai, Teluk Bayur Subdistrict, Berau Regency, from the perspective of Islamic law. This study aims to describe and analyse the operational mechanisms and socio-economic factors that drive these practices, as well as to assess their compatibility with Islamic law principles, in order to formulate a Sharia-based ethical and juridical framework as an alternative solution to informal mining practices in the community. This study is a field study of a qualitative nature. Primary data was collected through direct observation, in-depth interviews, and field documentation, combining normative and sociological approaches. Data analysis was conducted in three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that corridor mining takes place through informal cooperation between landowners and heavy equipment miners as a strategy for economic survival. Although it provides short-term benefits, this practice is illegal under positive law and is carried out in the IUP area of other companies. From an Islamic law perspective, this practice is not justified because coal is al-milkiyyah al-'ammah (public property) that must be managed by the state for the common good. This study emphasises the need to strengthen state governance and educate the community about sharia and environmental ethics.